Pneumoperitoneum in laparoscopic surgery: Comparison of the effect on gastric and intestinal motility in pediatric and adult rats - Alıcı, Umut; Unlu, Ahmet; Aydın, Yasemin; Tokar, Baran (Journal of Surgery and Medicine, 2019)
Aim: There are limited data on how pneumoperitoneum used during laparoscopy affects gastric and intestinal motility in children compared to adults. The aim of this experimental study is to measure and compare the effects of pneumoperitoneum on the gastric and small intestinal motility among children and adult rats. Methods: The study was conducted with 4 groups: Groups 1 and 2 (n=8 and 7, respectively) comprised pediatric rats while Groups 3 and 4 (n= 10 and 10, respectively) included adult rats. Pneumoperitoneum was achieved in Groups 1 and 3. Laparotomy was performed in Groups 2 and 4. The duration of procedure was 90 minutes in all groups. CO2 (Thermoflator, Karl-Storz, Germany) insufflation pressure was maintained at 5 mHg-0.5 ml/min. Postoperative gastric and intestinal motility studies were performed in all groups. Contractile responses to Acetylcholine and potassium chloride (at a dose range of 10-8 to 10-3 mM) were recorded (Isometric Transducer, Biopac, USA). Data Collection Analysis System (MP100 Biopac, USA) was used to analyze the data. Results: The lowest contraction response was obtained in group 1 for both the stomach and intestine. The responses of pediatric groups to potassium chloride and acetylcholine were lower than those of adult groups, but there was no significant difference among the 4 groups (P>0.05). Conclusion: This study may suggest that in the similar setting for pediatric and adult age groups, pneumoperitoneum does not significantly adversely affect gastric and small intestinal motility in children. Future studies should aim to investigate the effects of pneumoperitoneum on gastric and intestinal motility at different ages, weights, types of anesthesia, intra-abdominal pressures and operative durations.